2018
DOI: 10.3389/fimmu.2018.00833
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Invariant Natural Killer T Cells Redirects the Inflammatory Response in Neonatal Sepsis

Abstract: Sepsis is the third leading cause of death in the neonatal population, due to susceptibility to infection conferred by immaturity of both the innate and adaptive components of the immune system. Invariant natural killer T (iNKT) cells are specialized adaptive immune cells that possess important innate-like characteristics and have not yet been well-studied in septic neonates. We hypothesized that iNKT cells would play an important role in mediating the neonatal immune response to sepsis. To study this, we subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This is a limitation of our study and should be part of future research work. Sepsis is a systemic inflammatory response syndrome caused by infection [ 22 , 23 ]. The release of inflammatory cytokines plays a crucial role in the process of sepsis myocardial injury [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a limitation of our study and should be part of future research work. Sepsis is a systemic inflammatory response syndrome caused by infection [ 22 , 23 ]. The release of inflammatory cytokines plays a crucial role in the process of sepsis myocardial injury [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effect of rhTM on the severity of sepsis. We randomly assigned mouse pups into four groups: non-septic control (vehicle [Veh]-pretreated normal saline IP administration, Veh-Veh) group, Veh-treated septic (Veh-CS) group, and rhTM pretreated septic (rhTM3-CS or rhTM10-CS) groups, based on the method used in a prior study 24 .…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of direct activation of immune cells, Bolognese et al have reported a protective effect of activating Invariant Natural Killer T (iNKT) cells in neonatal sepsis. In their study, intraperitoneal injection of the iNKT stimulator KRN7000 30 h prior to sepsis induction resulted in better outcomes in inflammation, lung injury, and survival by increasing systemic levels of TGF-β1 [28]. All these studies have illustrated that preconditioning the immune response is effective in sepsis protection, even in neonatal mice.…”
Section: Discussionmentioning
confidence: 99%